Stmol: A component for building interactive molecular visualizations within streamlit web-applications - Nápoles-Duarte, J.M.; Biswas, Avratanu; Parker, Mitchell I.; Palomares-Baez, J.P.; Chávez-Rojo, M. A.; Rodríguez-Valdez, L. M. (Frontiers in Molecular Biosciences, 2022)
Streamlit is an open-source Python coding framework for building web-applications or "web-apps" and is now being used by researchers to share large data sets from published studies and other resources. Here we present Stmol, an easy-to-use component for rendering interactive 3D molecular visualizations of protein and ligand structures within Streamlit web-apps. Stmol can render protein and ligand structures with just a few lines of Python code by utilizing popular visualization libraries, currently Py3DMol and Speck. On the user-end, Stmol does not require expertise to interactively navigate. On the developer-end, Stmol can be easily integrated within structural bioinformatic and cheminformatic pipelines to provide a simple means for user-end researchers to advance biological studies and drug discovery efforts. In this paper, we highlight a few examples of how Stmol has already been utilized by scientific communities to share interactive molecular visualizations of protein and ligand structures from the Protein Data Bank, ChEMBL, and other resources. We hope Stmol will be used by researchers to build additional open-sourced web-apps to benefit current and future generations of scientists.